2011
DOI: 10.1101/lm.2049511
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioid receptors mediate where fear is expressed following extinction training

Abstract: Six experiments used a within-subjects renewal design to examine the involvement of kappa opioid receptors (KORs) in regulating the expression and recovery of extinguished fear. Rats were trained to fear a tone conditioned stimulus (CS) via pairings with foot shock in a distinctive context (A). This was followed by extinction training of the CS in a second context (B). Finally, all rats were tested for fear to the tone in the extinction context (ABB) and the training (ABA) or a novel (ABC) context. Intracerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…However, the extended inactivation of KOR that results from the administration of these KOR antagonists makes it impossible to know from those studies if the drug treatment interfered with the acquisition or with the expression of the leaned fear response. In a third study, central administrations of norBNI after a discriminative fear conditioning procedure had no effect on subsequent expression of fear [47]. In contrast to this most recent study, we report in this paper that contextual fear expression at Day 9 was weakly attenuated in shock rats that had received a post-shock injection of 30 mg/kg norBNI.…”
Section: Discussioncontrasting
confidence: 90%
“…However, the extended inactivation of KOR that results from the administration of these KOR antagonists makes it impossible to know from those studies if the drug treatment interfered with the acquisition or with the expression of the leaned fear response. In a third study, central administrations of norBNI after a discriminative fear conditioning procedure had no effect on subsequent expression of fear [47]. In contrast to this most recent study, we report in this paper that contextual fear expression at Day 9 was weakly attenuated in shock rats that had received a post-shock injection of 30 mg/kg norBNI.…”
Section: Discussioncontrasting
confidence: 90%
“…Aside from alcohol dependence and withdrawal, there is emerging evidence for the role of the DYN in fear conditioning, and relapse to drugs of abuse . One study showed that nor-BNI could block fear reinstatement, while U50,488 could potentiate fear renewal (Cole et al, 2011). Another study found that the KOR antagonists nor-BNI and JDTic could attenuate conditioned fear in the fear-potentiated startle paradigm (Knoll et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The extinguished fear can relapse when the subject is presented with a conditioned stimulus (CS) in the same context in which the fear conditioning was performed (ABA renewal) or in a third context distinct from the context where the fear conditioning or extinction was carried out (ABC renewal). Although both ABA and ABC renewal demonstrate the context-dependency of extinction learning, their mechanisms and manifestations have been shown to differ clearly in several aspects [8]–[14]. The dorsal hippocampus plays a critical role in ABC renewal [15], [16], but not ABA renewal [4], [17].…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal hippocampus plays a critical role in ABC renewal [15], [16], but not ABA renewal [4], [17]. In addition, blockade of kappa opioid receptor in the ventral hippocampus has a significant effect on ABA renewal, but not ABC renewal [7], [8]. Thus, it is important to study these two forms of fear renewal independently.…”
Section: Introductionmentioning
confidence: 99%